Recurrent Primary Sclerosing Cholangitis: Current Understanding, Management, and Future Directions - Leung, Kristel K.; Deeb, Maya; Fischer, Sandra E.; Gulamhusein, Aliya (Seminars in Liver Disease, 2021)
Patients with primary sclerosing cholangitis (PSC) constitute 5 to 15% of patients listed for liver transplantation worldwide. Although post-transplant outcomes are favorable, recurrent PSC (rPSC) occurs in an important subset of patients, with higher prevalence rates reported with increasing time from transplant. Given its association with poor graft outcomes and risk of retransplant, effort has been made to understand rPSC, its pathophysiology, and risk factors. This review covers these facets of rPSC and focuses on implicated risk factors including pretransplant recipient characteristics, inflammatory bowel-disease-related factors, and donor-specific and transplant-specific factors. Confirming a diagnosis of rPSC requires thoughtful consideration of alternative etiologies so as to ensure confidence in diagnosis, management, subsequent risk assessment, and counseling for patients. Unfortunately, no cure exists for rPSC; however, future large-scale efforts are underway to better characterize the natural history of rPSC and its associated risk factors with hopes of identifying potential key targets for novel therapies.
Keywords: recurrent primary sclerosing cholangitis; posttransplant complications; inflammatory bowel disease